2004
DOI: 10.1007/s00240-004-0445-3
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal transport of an obdurate anion: oxalate

Abstract: In this review, we focus on the role of gastrointestinal transport of oxalate primarily from a contemporary physiological standpoint with an emphasis on those aspects that we believe may be most important in efforts to mitigate the untoward effects of oxalate. Included in this review is a general discussion of intestinal solute transport as it relates to oxalate, considering cellular and paracellular avenues, the transport mechanisms, and the molecular identities of oxalate transporters. In addition, we review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
85
0
12

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(99 citation statements)
references
References 170 publications
2
85
0
12
Order By: Relevance
“…The fi rst peak of oxalate absorption could not be recorded in patients with a gastrectomy (12,13,93). Due to the tight epithelium, oxalate transport in the stomach is most likely transcellular (93). Immunocytochemical fi ndings of the presence of an oxalate transporter, sulfate anion (SO 4 2-) transporter Sat-1 (Slc26a1), in the oxyntic cells of the rat stomachs support claims in favour of this type of transport.…”
Section: Oxalate-handling Transporters and Their Role In Hyperoxalurimentioning
confidence: 93%
See 3 more Smart Citations
“…The fi rst peak of oxalate absorption could not be recorded in patients with a gastrectomy (12,13,93). Due to the tight epithelium, oxalate transport in the stomach is most likely transcellular (93). Immunocytochemical fi ndings of the presence of an oxalate transporter, sulfate anion (SO 4 2-) transporter Sat-1 (Slc26a1), in the oxyntic cells of the rat stomachs support claims in favour of this type of transport.…”
Section: Oxalate-handling Transporters and Their Role In Hyperoxalurimentioning
confidence: 93%
“…A few studies have shown that the stomach could be an important locus of oxalate absorption. The fi rst peak of oxalate absorption could not be recorded in patients with a gastrectomy (12,13,93). Due to the tight epithelium, oxalate transport in the stomach is most likely transcellular (93).…”
Section: Oxalate-handling Transporters and Their Role In Hyperoxalurimentioning
confidence: 96%
See 2 more Smart Citations
“…The majority of anionic oxalate is thought to be absorbed via a paracellular route ( Figure 1) (15). Apical and basolateral transporters have also been demonstrated to have oxalate-transporting activity in vitro.…”
Section: Oxalate Biologymentioning
confidence: 99%